2018
DOI: 10.1016/j.crvi.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine- and amphetamine-regulated transcript (CART) peptide in the enteric nervous system of the porcine esophagus

Abstract: Cocaine- and amphetamine-regulated transcript peptide (CART) is widely distributed within the central and peripheral nervous system. In the brain, CART is considered as the main anorectic peptide involved in the regulation of food intake. Contrary to the central nervous system, a lot of aspects connected with the distribution and functions of CART within the enteric nervous system (ENS) still remain unknown. The aim of the present study was to investigate, for the first time, the population of CART-like immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
5
10
0
Order By: Relevance
“…In the current study, the largest number of NOS-positive neurons was observed in the myenteric plexus, the outer submucosal plexus contained slightly fewer NOS-immunoreactive neurons, while the inner submucosal plexus exhibited the smallest quantity of NOS-containing neurons. In the available literature, there are few results concerning the distribution of nitrergic nervous structures in the porcine ENS, especially in the small intestine [5,33]. The current results are congruent with a previous study conducted in pigs [6] in which, as in the present study, more numerous NOS-positive neurons were found in the myenteric plexus within the small intestine [5].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, the largest number of NOS-positive neurons was observed in the myenteric plexus, the outer submucosal plexus contained slightly fewer NOS-immunoreactive neurons, while the inner submucosal plexus exhibited the smallest quantity of NOS-containing neurons. In the available literature, there are few results concerning the distribution of nitrergic nervous structures in the porcine ENS, especially in the small intestine [5,33]. The current results are congruent with a previous study conducted in pigs [6] in which, as in the present study, more numerous NOS-positive neurons were found in the myenteric plexus within the small intestine [5].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, for the first-time co-localization of nNOS with other biologically-active substances in animals with high glucose levels was described. As shown in previous studies, nitric oxide is a commonly occurring neurotransmitter within different parts of gastrointestinal tract [5,26,27,28]. Interspecies differences in the localization of nNOS-positive neurons inside the gastrointestinal tract were observed, both in each plexus as well as particular fragments of digestive tract.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We can speculate that dysregulation of CART expression probably depends on both the pathological condition and the region of the GIT studied. Moreover, it is well established that CART in enteric neurons of the porcine GIT [54,77], as well as human [68], can colocalize with a wide range of other neurotransmitters. The coexistence of CART and nNOS or VIP in the same nervous structures can suggest a similar role of colocalized neuropeptides.…”
Section: Discussionmentioning
confidence: 99%
“…In large mammals, the organization of the ENS in the esophagus and stomach is similar to rodents [ 38 , 39 , 40 ], although some authors have described three types of the enteric plexuses (such as in the intestine—see below) in the porcine stomach [ 41 ]. The only exception are ruminants, in which only one type of the enteric ganglia (myenteric ganglia) has been described in the forestomach.…”
Section: Anatomy Of the Enteric Nervous Systemmentioning
confidence: 99%